A comparative study of various methods for detection of IL28B rs12979860 in chronic hepatitis C. (19th May 2017) - Monavari, Seyed Hamidreza; Fateh, Roohollah; Vaziri, Farzam; Rahimi Jamnani, Fatemeh; Anvari, Enayat; Sadeghi, Farzin; Afrough, Parviz; Behrouzi, Ava; Sakhaee, Fatemeh; Meidaninikjeh, Sepideh; Mollaie, Hamidreza; Hadizadeh Tasbiti, Alireza; et al.
Abstract: Interleukin-28B ( IL28B ) single-nucleotide polymorphisms (SNPs) constitute important host-related factors influencing the response rate to Hepatitis C virus (HCV) standard antiviral therapy. In the last few years, several new technologies for SNP detection have been developed. However, the sensitivity and specificity of various methods are different and needs evaluation. Five different methods (resolution melting curve [RMC], polymerase chain reaction-restriction fragment length polymorphism [PCR-RFLP], PCR-sequencing analysis, amplification refractory mutation system [ARMS], and zip nucleic acid probe-based real-time PCR [ZNA]) were developed for genotyping rs12979860 associated with IL28B . In this study, limit of detection (LD), costs and turnaround time of these methods were compared in 350 subjects. As for IL28B rs12979860 polymorphisms, 348/350 (99.4%) samples were consistent among the five methods, while results for 2/350 (0.57%) samples were concordant by ZNAs and PCR-sequencing, and discordant by other methods. Without considering the cost of DNA extraction, the price of each reaction for ARMS-PCR, RMC, PCR-RFLP, ZNA and PCR-sequencing were respectively: US3.10, US5.0, US5.50, US8.50 and US17.0. RMC was the fastest method, while the ZNA method was easy to use, reliable and effective. Lower LD was determined to be 50–60 copies/μL for the PCR-RFLP, RMC and ARMS-PCR assays; whilst ZNA assay was able to detect 2–3 copies/μL. In conclusion, in the current study, all four methods are suitable for IL28B rs12979860 genotyping, but the ZNA assay can be a reliable tool. Due to its lower LD for SNP identification, this method is better than others for detecting this type of polymorphism.